BIAS BUDAYA DALAM PELAYANAN KONSELING - Erida Erida (Al Irsyad : Jurnal Bimbingan Konseling Islam, 2019)
Counseling is a process to help individuals overcome the obstacles to the development of their personal abilities in order to develop optimally. The counseling process can occur at any time through individual relationships to express and to appreciate the individual's unique needs, motivations, and potentials. Cross-cultural counseling involves counselors and clients who come from different cultural backgrounds, and therefore the counseling process is very vulnerable by the occurrence of cultural biases on the part of the counselor which results in ineffective counseling. In order for counseling to run effectively, the counselor is required to have sensitivity to culture and escape from cultural biases, and to have skills that are culturally responsive. Then counseling is seen as a cultural encounter (cultural ecounter) between counselor and client.